Can Aggressive Marketing Cause an Ethical Dilemma? - Hashem , Tareq N. (International Journal of Membrane Science and Technology, 2023)
Current aimed to answer the question of whether aggressive marketing (Intensity, Frequency, Intrusiveness, Personalization and Persistence) can be seen as an intruder to the ethical value of marketing tactics and strategies. Theoretical framework: Many organizations are seeking multiple approaches to market their product/services. Come of them do not give much attention to the marketing approach as long as it may comeback with profit and promotion to their products. One of these approaches are now called aggressive marketing which is based on organization taking risks and proactive tactics in order to guarantee its share in the market. Design/Methodology/Approach: Through quantitative methodology and a distribution of a questionnaire on (293) managers and officer within companies registered with the Companies Control Department. The answer to the question is the fact that YES, aggressive marketing can be a source of an ethical dilemma and companies must be careful not to cross ethical or legal boundaries in their marketing efforts, such as making false or misleading claims, using deceptive advertising, or engaging in unfair competition practices. Findings: Results also indicated that in some cases, aggressive of marketing can turn into harassment, with individuals receiving multiple phone calls, emails or direct mail that creates a sense of discomfort, anxiety or fear. Such marketing practices could be seen as abusive, unethical, and illegal. The level of intensity in aggressive marketing should be carefully calibrated to balance the need to generate sales with the need to maintain customer trust and brand reputation over the long term. Research, Practical & Social Implications: The theoretical implications of current study would involve examining the relationship between aggressive marketing tactics and their impact on the ethical framework of businesses, organizations and their stakeholders. On a practical level, the study’s findings could have significant implications for the way in which companies approach marketing and promotions. Originality/value: The study could also highlight the importance of establishing clear ethical standards and guidelines for businesses and marketers, in order to prevent negative impact on customers and public perception.